Karakteristik Pasien Desensitisasi Cepat di RSUP Prof. Dr. I. G.N.G Ngoerah Denpasar Tahun 2022-2024 - Yogi Haditya; Ketut Suardamana (Syntax Corporation Indonesia, 2024)
Rapid desensitization is the primary management for patients with hypersensitivity reactions to certain medications when no alternative therapy to the primary drug is available. The rapid desensitization process is routinely performed at RSUP Prof Ngoerah Denpasar, but there is little data on the characteristics of patients undergoing this procedure. This study used a cross-sectional descriptive design with a total sample of 24 patient. The research samples were collected using consecutive sampling methods from patient medical records. The study was conducted at the inpatient unit of RSUP Prof. Dr. I.G.N.G Ngoerah from January 2022 to June 2024. The inclusion criteria were adult patients aged ≥ 18 years who underwent the rapid desensitization protocol and had complete medical records. The study found that the sample was predominantly female (62.5%) with an average age of 42.6 years (SD ± 18.0 years). The most common underlying disease among desensitization patients was Tuberculosis, affecting 13 individuals (54.1%), with the most frequent manifestation of hypersensitivity reactions being pruritus-urticaria in 100% of patients. The categories of drugs for which rapid desensitization was performed included antituberculosis drugs (OAT) in 14 patients (58.3%), with a few patients receiving NSAIDs (4.2%) and antipyretics (8.3%). Among the total 24 patients undergoing desensitization, a positive reaction was found in 9 patients (37.5%). The average time to drug exposure until the hypersensitivity reaction occurred was 10.1 days with a standard deviation of ± 11.2 days.